Capital structure of government-linked companies in Malaysia - Ting I.W.K.; Lean H.H. (2023)
This study investigates the cross-sectional variation in leverage among publicly listed Government Linked Companies (GLCs) and non-GLCs (NGLCs) in Malaysia for the period from 1997 to 2008. The study uses balanced panel data with multivariate regression as the method of analysis. Results reveal that the GLCs are consistently more heavily leveraged than NGLCs. The findings indicate a significantly positive association between debt ratio (DR) and tangible assets but a negative relationship between DR and profitability for both GLCs and NGLCs. However, firm size is significantly negatively related to DR for GLCs and significantly positively related to DR for NGLCs. The study also finds that tangible assets and profitability have an inverse relationship with long-term debt. There is a significant negative association between asset structure, profitability and short-term debt. However, firm growth and cash flow have no influence on the determination of short-term and long-term debt. Asian Academy of Management and Penerbit Universiti Sains Malaysia, 2011.